Rancang Bangun Bilah Turbin Angin Sumbu Horizontal Tipe Taperless Dengan Airfoil Psu94-097 Menggunkan Material Kayu Nangka (Artocapus Heterophyllus) - Rifki Maulana Sidik; Kardiman Kardiman; Najmudin Fauji (Peneliti.net, 2022)
Wind energy is a renewable alternative energy source that is environmentally friendly. As in indonesia, the wind potential is very capable of being utilized or develoved for renewable energy, whre the average wind speed in indonesia is 2 m/s – 8 m/s with the wind speed capable of driving wind turbines. Turbines have an important component, namely blades, these blades convert wind energy to kinetic energy. The purpose of the research on design of Horizontal Axis Wind Turbine Taperless type with Airfoil PSU94-097 using jackfruit wood is to determine the process of material is to determine the process of designing, manudacturing and tasting. Where starting with the selection of the airfoil is PSU94-097 with a Cl/Cd value of 138.56 and a CP/TSR value of 46%. 2D and 3D bar design are made in Solidworks software by entering coordinate to simplity the manufacturing process, namely manufacturing. The last stage is testing the blades on the wind turbine, where the total test for three days produces 371.54 Wh of power with the highest wind speed of 12.46 m/s.